Combined Anticancer Effect of Plasma-Activated Infusion and Salinomycin by Targeting Autophagy and Mitochondrial Morphology - Ando, Takashi; Suzuki-Karasaki, Manami; Suzuki-Karasaki, Miki; Ichikawa, Jiro; Ochiai, Toyoko; Yoshida, Yukihiro; Haro, Hirotaka; Suzuki-Karasaki, Yoshihiro (Frontiers in Oncology, 2021)
Non-thermal atmospheric plasma (NTAP)-activated liquids have emerged as new promising anticancer agents because they preferentially injure malignant cells. Here, we report plasma-activated infusion (PAI) as a novel NTAP-based anti-neoplastic agent. PAI was prepared by irradiating helium NTAP to form a clinically approved infusion fluid. PAI dose-dependently killed malignant melanoma, and osteosarcoma cell lines showed much lower cytotoxic effects on dermal and lung fibroblasts. We found that PAI and salinomycin (Sal), an emerging anticancer stem cell agent, mutually operated as adjuvants. The combined administration of PAI and Sal was much more effective than single-agent application in reducing the growth and lung metastasis of osteosarcoma allografts with minimal adverse effects. Mechanistically, PAI explicitly induced necroptosis and increased the phosphorylation of receptor-interacting protein 1/3 rapidly and transiently. PAI also suppressed the ambient autophagic flux by activating the mammalian target of the rapamycin pathway. PAI increased the phosphorylation of Raptor, Rictor, and p70-S6 kinase, along with decreased LC3-I/II expression. In contrast, Sal promoted autophagy. Moreover, Sal exacerbated the mitochondrial network collapse caused by PAI, resulting in aberrant clustering of fragmented mitochondrial in a tumor-specific manner. Our findings suggest that combined administration of PAI and Sal is a promising approach for treating these apoptosis-resistant cancers.